Diversity of Bivalvia in Estuarine of Suramadu Bridge of Surabaya - Viola Atlanta; Reni Ambarwati; Mujiono Nova (Masyarakat Moluska Indonesia, 2022)
The coast of the Suramadu Bridge is one of the important areas that has function as a route for transportation, recreation, as well as a protected area. However, the data of aquatic biota is rarely studied. One of them is bivalves. This research was conducted in February 2021 with the aim to analyze the diversity of bivalves in the Suramadu Coast. Observations and sampling were carried out in 3 transects 5 x 5 m based on different habitats. Five species of bivalves (Mimachlamys sanguinea, Anadara rhomboidalis, Tegillarca granosa, Barbatia trapezina, and Atrina pectinata) from three families (Pectinidae, Arcidae, and Pinnidae) were identified. The results of the community index show the individual distribution pattern and community stability in the medium category, there is a dominant species (Anadara rhomboidalis) but without significant differences in the number of individuals. This shows that the bivalves community is in a state of stress. A. rhomboidalis has the greatest role in the stability of the community, which can be seen from the value of the Important Value Index and the total volume of the shell. Recently, there are only two species that can be used sustainably, namely T. granosa and A. rhomboidalis.